Political Spirits at the Dawn and Dusk: Exploring History Through Literature (NPRC Journal of Multidisciplinary Research, 2025)
The introduction of democracy in 1951 brought the enjoyment of fundamental rights for the citizens and the spirited election environment. However, the spirits could not last longer as an encroachment on democracy was forwarded by King in 1960, which altered ecstasy into resistance and rebellion. The research explores the political spirits prevalent at the beginning of the first decade of infant democracy and the rise of agitation against the despotic regime at the end of the decade, which covers the period of 2007 BS to 2017 BS through Govinda Bahadur Malla's "Chunab" and B. P. Koirala's "Ek Raat." The data on political aspects have been purposefully selected and situated against the historical document. Since this study employs the exploratory qualitative approach, primary data from the short stories are approached from the lens of new historicism, the theory of power and resistance, and the concept of state apparatus. However, literary data provide a broader horizon of historical events. The themes of election and rebellion are contrasted to discover the contrary spirits of the same decade. The results indicate that the dawn of the infant democracy is full of enthusiasm with the spirits caused by the fervor of election. In contrast, the dusk of democracy is full of despair and agitation, giving rise to resistance and rebellion. The results indicate that approaching history and historical documents through the lens of literature set simultaneously can broaden the horizon of understanding of historical events.